ANGGARAN PARTISIPATIF DALAM MENUNJANG KINERJA APARATUR PEMERINTAH DAERAH - Usman, Ernawaty; Paranoan, Selmita (Universitas Brawijaya, 2013)
Abstract: Participative Budgeting in Supporting performance of Local Government Officials. The purpose of this research is to understand the effect of participative budgeting on supporting performance of governmental organization with culture and organization commitment as moderating variable Local government officials of Kabupaten Sigi. Survey method was used in this research. The result shows that budget participate positively related to performance of local government officials. Organization commitment and organization culture are also related positively to budgetÂ slack. Organization commitment and organization culture as moderating variable support the relation of budget participate on performance of local government officials.Abstrak: Anggaran Partisipatif dalam Menunjang Kinerja Aparatur Pemerintah Daerah. Penelitian ini bertujuan untuk mengetahui pengaruh Anggaran Partisipatif dalam menunjang Kinerja Aparatur Pemerintah Daerah dengan budaya dan komitmen organisasi sebagai variabel moderasi dalam Lingkup Pemerintah Daerah Kabupaten Sigi. Metode Penelitian yang digunakan adalah metode survey. Hasil penelitian menunjukkan bahwa partisipasi anggaran berhubungan positif terhadap Kinerja Aparatur Pemerintah Daerah. Komitmen Organisasi dan Budaya Organisasi juga memiliki hubungan positif terhadap senjangan anggaran. Komitmen Organisasi dan Budaya OrganisasiÂ sebagai variabel moderasi memperkuat hubungan partisipasi anggaran terhadap Kinerja Aparatur Pemerintah Daerah.